Pengaruh Resiko Kredit dan Likuiditas Terhadap Kinerja Bank di Indonesia - Riza, Nadilla Marta; Satria, Doni; Artha, Dwirani Puspa (Universitas Negeri Padang, 2024)
This research was conducted to identify the effect of credit risk and liquidity risk on bank performance in Indonesia. The object of this research is conventional commercial banks listed on the Financial Services Authority with the research period using quarterly data from 2019 to 2022. The population in this research is 106 banks with a sample of 68 banks obtained from the purposive sampling method. From the 68 bank samples, sub-samples of banks were also formed based on bank groups consisting of state-owned banks and BPD, national private banks, and mixed banks (national and foreign private) with the aim of seeing comparisons of panel data regression results using Eviews 12 software. Based on analysis that has been carried out based on the regression results of 68 bank samples as a whole, shows that partial research results show that credit risk has a negative but not significant effect or in other words has no effect on bank performance in Indonesia and liquidity risk has a negative effect on bank performance in Indonesia.